2009
DOI: 10.5205/reuol.581-3802-1-rv.0304200914
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos condutores de motocicleta vítimas de acidentes de trânsito atendidos em hospital de urgência

Abstract: Objectives: to characterize drivers involved in motorcycle accidents and identify injuries according to body region. Methodology: this is about a descriptive exploratory study, prospective, from quantitative approach, performed in the Monsenhor Walfredo Gurgel Hospital Complex (HMGW), from Natal city, Brazil. The population consisted of 4.511 victims of motorcycle accidents attended in 2006. The sample of 371 patients was defined after the inclusion from criteria and calculation of 5% of the population. To col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
2
Order By: Relevance
“…A Escala de Coma de Glasgow (ECG) é uma ferramenta adotada mundialmente como um padrão de avaliação do nível de consciência e de classificação do traumatismo crânio-encefálico (FARIAS et al, 2009a). Visto como um método simples e rápido para avaliar a função cerebral, leva em consideração a abertura ocular, a melhor resposta verbal e a melhor resposta motora que o paciente apresenta, cujos escores são: a) 13-15: indica uma lesão e gravidade leve; b) 9-12 indica uma lesão e gravidade moderada e c) 3-8 indicando um estado grave.…”
Section: R Bras CI Saúde 18(1):3-10 2014unclassified
“…A Escala de Coma de Glasgow (ECG) é uma ferramenta adotada mundialmente como um padrão de avaliação do nível de consciência e de classificação do traumatismo crânio-encefálico (FARIAS et al, 2009a). Visto como um método simples e rápido para avaliar a função cerebral, leva em consideração a abertura ocular, a melhor resposta verbal e a melhor resposta motora que o paciente apresenta, cujos escores são: a) 13-15: indica uma lesão e gravidade leve; b) 9-12 indica uma lesão e gravidade moderada e c) 3-8 indicando um estado grave.…”
Section: R Bras CI Saúde 18(1):3-10 2014unclassified
“…Regarding the education, there was a predominance of victims with complete high school, which is different from a study (FARIAS et al, 2009) that dealt with the severity of the injury with motorcycle drivers victims of traffic accident in the state of RN, Brazil, where it showed that, from 371 victims, 37.47% had incomplete primary education, and only 26.68% had completed high school. It is believed that the increase of the victims' educational level is due to the increased accessibility to the educational institutions, and because the job market demand, which is larger for more educated people.…”
Section: Discussionmentioning
confidence: 51%
“…En lo tocante a la enseñanza, fue notable el predominio de víctimas con enseñanza primaria incompleta corroborando otro estudio (14) en que, de las 371 víctimas estudiadas, el 37,47% también tenía enseñanza primaria incompleta. Es perceptible que, incluso con los avances en las políticas de acceso a la educación, enseñanza básica y superior, muchas personas todavía no han concluido los estudios.…”
Section: Discussionunclassified